2021
DOI: 10.1186/s13613-021-00809-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher anticoagulation targets and risk of thrombotic events in severe COVID-19 patients: bi-center cohort study

Abstract: Background Thromboprophylaxis of COVID-19 patients is a highly debated issue. We aimed to compare the occurrence of thrombotic/ischemic events in COVID-19 patients with acute respiratory distress syndrome (ARDS) treated with either prophylactic or therapeutic dosage of heparin. All patients referred for COVID-19 ARDS in two intensive care units (ICUs) from two centers of a French tertiary hospital were included in our cohort study. Patients were compared according to their anticoagulant treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…These findings suggest vascular micro-thrombotic disease as a primary factor for mortality in critically ill COVID-19 [ 6 , 14 ]. Therefore, some authors supported the systematic use of curative anticoagulation upon admission to intensive care unit (ICU) [ 15 ], a strategy that has been reported to decrease mortality in severe COVID-19 [ 8 , 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest vascular micro-thrombotic disease as a primary factor for mortality in critically ill COVID-19 [ 6 , 14 ]. Therefore, some authors supported the systematic use of curative anticoagulation upon admission to intensive care unit (ICU) [ 15 ], a strategy that has been reported to decrease mortality in severe COVID-19 [ 8 , 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though AC has been shown to prevent macrothrombotic complications (23,24), intermediate doses did not worsen or modify the mortality outcome in these studies likely because treatment was introduced too late into the course of the disease. Indeed, it is clear that microthrombosis/lung obstruction is pathognomonic of COVID-19 worsening and hypoxemia, in contrast to most other respiratory viral infections.…”
Section: Discussionmentioning
confidence: 86%
“…Higher anticoagulation targets were considered to protect from thrombotic events in the most severely affected patients [ 62 , 37 ]. Helms et al demonstrated that anticoagulation was not associated with increased bleeding, differences in ICU mortality or length of stay compared with patients in regular prophylaxis [ 64 , 65 ]. In an observational retrospective study, Paranjpe et al [ 66 ] assessed the association between administration of in-hospital anticoagulation and survival in a large cohort of hospitalized patients with COVID-19 and showed that therapeutic anticoagulation may be associated with improved outcomes among patients hospitalized with COVID-19 (reduced risk of mortality: adjusted HR of 0.86 per day, 95% confidence interval 0.82–0.89, p < 0.001).…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 99%